Short Communication Cathodic Efficiency of Industrial Chromium Plating - Haque, Inam-ul-; Khan, Asim; Rasheed, Abdul (Biological Sciences - PJSIR, 2006)
Current efficiency of hard chrome plating bath was studied. Experiments were carried out using industrial grade chromic acid. The best results were obtained from the chrome plating bath comprising chromic acid 300-350 g/l, sodium silicofluoride 5-6 g/l, CrO3/H2SO4 ratio of 125 : 1, at current density 12 A/dm and temperature 30-35 °C. The current efficiency of the bath was 32%.